The Effectiveness of Interactive Media in Improving Compliance with Medication for Hypertension Patients - Cek Masnah; Atik Suharti; Daryono Daryono (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Irregular treatment of hypertension has the potential to increase blood pressure again, and also has the potential to cause more serious complications. Understanding hypertension is important to improve adherence to treatment for patients with hypertension. One of the efforts to increase compliance is using interactive media as a medium for health education. The research design was quasi-experimental with a non-randomized pre-test and post-test control group, with a sample of 60 people in the intervention group and 60 people in the control group. The results showed that: there was a significant difference (Asymp. Sig. = 0.002) regarding family support between the intervention group and the control group; there was a significant difference (Asymp. Sig. = 0.000) regarding adherence between the Control Group and the Intervention Group; there were significant differences regarding family support and adherence between before and after the intervention; interactive media effectively increased family support with a moderate level of effectiveness (51.81%) and increased compliance with a moderate level of effectiveness (55.83%). In using interactive media as an extension media, it should pay attention to regional conditions and social conditions of the community, and should be combined with other media. Abstrak: Pengobatan hipertensi yang tidak teratur berpotensi meningkatnya kembali tekanan darah, juga berpotensi menimbulkan komplikasi yang lebih serius. Pemahaman tentang hipertensi penting untuk meningkatkan kepatuhan berobat penderita hipertensi. Salah satu upaya untuk meningkatkan kepatuhan adalah penggunaan media interaktif sebagai media penyuluhan kesehatan. Desain penelitian adalah quasi eksperimen dengan non-randomized pre-test and post-test control group, dengan sampel 60 orang kelompok intervensi dan 60 orang kelompok control. Hasil penelitian menunjukkan bahwa: terdapat perbedaan yang signifikan (Asymp. Sig. = 0,002) mengenai dukungan keluarga antara Kelompok Intervensi dan Kelompok Kontrol; terdapat perbedaan yang signifikan (Asymp. Sig. = 0,000) mengenai kepatuhan antara Kelompok Kontrol dan Kelompok Intervensi; terdapat perbedaan yang signifikan mengenai dukungan keluarga dan kepatuhan antara sebelum dan sesudah intervensi; media interaktif efektif meningkatkan dukungan keluarga dengan tingkat efektivitas sedang (51,81%) dan meningkatkan kepatuhan dengan tingkat efektivitas sedang (55,83%). Dalam menggunakan media interaktif sebagai media penyuluhan hendaknya memperhatikan kondisi wilayah dan kondisi sosial masyarakat, dan sebaiknya dikombinasikan dengan media lainnya